Does Food Safety Knowledge Influence Customer Expectation and Perception on Restaurant’s Quality Attributes? - Padmaningrum, Dwiningtyas; Fauza, Gusti; Karunia, Aulia Rahma; Juego, Bonn; Nursiwi, Asri; Ariviani, Setyaningrum; Prasetyo, Hari (Jurnal Teknologi Hasil Pertanian, 2023)
The number of restaurants has increased recently and leads to a pierce competition in this business. To be more competitive, restaurant owners need to pay more attention on customer satisfaction. This study is aimed to examine customer satisfaction in restaurants using three variables, namely food quality, services, and environment facilities in a restaurant. Unlike studies in this area the variables were evaluated using food safety criteria where the customers’s knowledge about food safety issues were measured to analyze whether it affects the customer perception and satisfaction. The importance-performance analysis (IPA) is used to explain which attributes that need to be improved after mapping the customer expectations and perceptions. Implementing IPA to could help restaurant owners to concentrate on improving the priority quality attributes, i.e., the attributes that are important for customers but have relatively low performance. A questionnaire with food safety perspective question were distributed to 400 customers and 395 questioner were completed. The IPA Diagram reveals that the higher the consumer's knowledge the more attributes were suggested to be improved.